IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI PADA MASA PANDEMI COVID-19 DI SMP PGRI 2 DENPASAR - Ni Putu Damiyani; Kadek Aria Prima Dewi PF; Ida Ayu Gde Wulandari (Upadhyaya : Jurnal Penelitian Pendidikan, 2023)
The COVID-19 pandemic has affected the education system in Indonesia, according to the SE of the Ministry of Education and Culture Number 4 of 2020 concerning the Implementation of Education in the Coronavirus Disease (Covid-19) Emergency Period. In this condition, all teachers or educators are required to replace learning using E-learning or through online media, including at SMP PGRI 2 Denpasar. The formulation of the problems that will be studied in this research are: (1) How is the planning of learning Hindu religion and manners during the Covid-19 pandemic at SMP PGRI 2 Denpasar?, (2) How is the implementation of learning Hindu religion and manners during the Covid pandemic? -19 at SMP PGRI 2 Denpasar?, (3) How is the evaluation of learning Hindu religion and manners during the Covid-19 pandemic at SMP PGRI 2 Denpasar?. This study aims to: (1) describe the planning of learning Hindu religion and manners during the Covid-19 pandemic, (2) Analyzing the implementation of Hindu religious learning and manners during the Covid-19 pandemic, (3) Analyzing how to evaluate Hindu religious learning and manners during the Covid-19 pandemic at SMP PGRI 2 Denpasar, the problems in this study were studied using constructivism theory and behaviorism theory. This study uses data collection techniques of observation, interviews, literature study, documentation. The data that has been collected was analyzed using qualitative descriptive analysis techniques through three stages of data reduction activities, data presentation, and conclusion drawing. Based on the results of research and data analysis, it shows that: (1) planning for learning Hinduism and manners during the Covid-19 pandemic at SMP PGRI 2 Denpasar through the stages of preparing the design of learning materials, preparing learning media and choosing Hindu religion and character learning methods in the time of the covid-19 pandemic. (2) the implementation of learning about Hindu religion and manners during the Covid-19 pandemic at SMP PGRI 2 Denpasar through preliminary activities, core activities, and closing activities. (3) evaluation of learning Hindu religion and manners during the Covid-19 pandemic at SMP PGRI 2 Denpasar through assessment of student knowledge, assessment of student attitudes and assessment of student skills. Keywords: Learning, Hindu religious education and manners, the Covid-19 pandemic